2008
DOI: 10.1002/jmri.21283
|View full text |Cite
|
Sign up to set email alerts
|

Source of low‐frequency fluctuations in functional MRI signal

Abstract: Purpose:To investigate the source of native low-frequency fluctuations (LFF) in functional MRI (fMRI) signal. Materials and Methods:Phase analysis was performed on tissue-segmented fMRI data acquired at systematically varying sampling rates.Results: LFF in fMRI signal were both native and aliased in origin. Scanner instability did not contribute to native or aliased LFF. Aliased LFF arose from cardiorespiratory processes and head motion. Native LFF did not arise from cardiorespiratory processes, but did so, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…BOLD LFF are known to be potentially confounded by a number of non-neural factors such as systemic cardio-vascular physiological variables, and artefacts such as motion. It has been noted that motion may affect LFF [18,19], but no systematic study on such effects exists. As sedation and light sleep may increase the propensity for head motion by reducing the subject's conscious control of head position, we hypothesised that LFF increases observed in human sedation studies may be mediated by sedation-induced increased head motion.…”
Section: Introductionmentioning
confidence: 97%
“…BOLD LFF are known to be potentially confounded by a number of non-neural factors such as systemic cardio-vascular physiological variables, and artefacts such as motion. It has been noted that motion may affect LFF [18,19], but no systematic study on such effects exists. As sedation and light sleep may increase the propensity for head motion by reducing the subject's conscious control of head position, we hypothesised that LFF increases observed in human sedation studies may be mediated by sedation-induced increased head motion.…”
Section: Introductionmentioning
confidence: 97%
“…The magnitude (or amplitude) of B-waves is inversely correlated with the volume buffering reserve of the intracranial compartment and directly correlated with measured resistance to cerebrospinal fluid (CSF) outflow (Rcsf), a reliable parameter describing CSF circulation. [8][9][10] The presence of prominent slow waves has been correlated with clinical improvement after shunting in normal pressure hydrocephalus (NPH). 9,11,12 In the context of severe traumatic brain injury (TBI), the presence of B-waves reflects active vasogenic modulation of Cerebral Blood Flow (CBF) and is associated with better prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies using near-infrared spectroscopy (NIRS) (10) have reported low-frequency oscillations (LFOs) of ∼0.04-0.1 Hz for oxygenated hemoglobin (HbO 2 ) and HbR in the brain consistent with those measured by BOLD (11). However, there is still no quantitative understanding of the relative direct contribution of spontaneous oscillations in cellular activity (neuronal and glial) vs. oscillations that reflect hemodynamic coupling (velocity and vessel diameter) (12) to the resting-state signal. It is also unclear how fluctuations in HbR progress through the vascular tree (13); whereas BOLD signals are believed to predominantly reflect postcapillary and venous compartments, recent evidence suggests that capillaries and arteries also contribute (14).…”
mentioning
confidence: 99%